Morfologia da micrópila e da superfície dos ovócitos de piracanjuba, Brycon orbignyanus (Osteichthyes, Characidae), sob microscopia eletrônica de varredura - Ganeco, Luciana Nakaghi [UNESP]; Nakaghi, Laura Satiko Okada (Universidade Estadual de Maringa, 2003)
This paper studied the morphology of oocytes of Brycon orbignyanus, (Osteichthyes, Characidae), through observation in Scanning Electron Microscopy (SEM). Fragments of the ovaries from adult females were collected. During the reproductive period, a hormonal induction in females was carried out to collect the oocytes after extrusion. The samples were fixed and processed for observation in SEM. Results showed that the oocytes of B. orbignyanus had a follicular epithelium formed by a single layer of cells with compressed shape, covering the whole radiatta zone that showed a smooth and regular surface with innumerable pores. The micropyle had a funnel-shaped, containing several furrows. The oocyte surface around the micropyle presented pores closer of each other than the other surface areas of radiatta zone.
Morphology of the micropyle and oocyte surface of piracanjuba, Brycon orbignyanus (Osteichthyes Characidae), with scanning electron microscopy
Keywords: Brycon orbignyanus; Micropyle; Morphology; Oocyte; Teleost; brycon orbignyanus; cell structure; cell surface; egg; female; fish; hormonal regulation; nonhuman; oocyte; reproduction; scanning electron microscopy; teleost; Characidae; Osteichthyes; Teleostei